Perioperative inflammatory response in patients with rheumatoid arthritis undergoing orthopaedic surgery - Lisowska, Barbara; Maśliński, Włodzimierz; Małdyk, Paweł (Archives of Medical Science, 2009)
Introduction: This study investigates the course of blood cytokine levels and CRP in patients with rheumatoid arthritis (RA) undergoing total knee replacement (TKR). Additionally, we set out to examine the relationship between cytokines IL-6, TGF-b1 and CRP and parameters such as body temperature, tourniquet time and blood loss. Material and methods: The study concerns 40 patients with RA undergoing total knee replacement (TKR). Operative and postoperative details were recorded, including circulation, ventilation, body temperature, tourniquet time under operation and postoperative blood loss. Peripheral vein blood was serially sampled; the first was obtained before anaesthesia and next at 6, 12, 24, 36 h after the end of surgery. IL-6, TGF-b1 and CRP were evaluated in blood and at the same time body temperature (°C) was measured. Results: In patients with RA undergoing TKR under regional anaesthesia, the levels of IL-6 and TGF-b1 in the peripheral blood were not significantly changed compared with the levels before operation. The rise of CRP protein concentration was achieved at first 36 h postoperatively. No significant changes in serum IL-6, TGF-b1 and CRP levels with regard to tourniquet time were found. The volume of blood loss was not associated with changes in cytokine and CRP blood concentrations either. A correlation between postoperative CPR levels and temperature was found. The body temperature remained elevated up to 36 h postoperatively. Conclusions: Our data indicate that high production of cytokines (IL-6, TGF-b1) present in chronic inflammation prevents further enhancement of cytokine synthesis triggered by surgery. The rise of CRP concentrations postoperatively and the significant correlation between CRP and temperature were addressed. The postoperative rise of temperature in the first 3 days following TKR may be a normal physiological response.